SY41-1BUILDING BRIDGES: NETWORKING TO ESTABLISH THE EXCHANGE OF CULTURALLY SENSITIVE ADDICTION TREATMENT MODALITIES AND RESEARCH. (September 2014) - Matsumoto, T.
Abstract : Toshihiko Matsumoto, M.D., Ph.D. along with Dr. C. Richard McKinley begins by presenting data on the following subjects as they pertain to Japan: Common topics shared by Japan and the U.S.: We share the same Illness. Overview of the Japanese Diagnostic Criteria found in ICD-10 Scope of the problem in Japan, addicted populations only. Differences between Japan and the U.S. are presented: Differing data regarding percentages of the addicted population which received treatment, and the respective number in recovery. Legal differences for confidentiality of chemical use history and criminal behavior and incarceration of addicts when they disclose their chemical use history to a helping professional. Tsukasa Mizusawa and Scott Johnson L.A.C. present and then Dr. Matsumoto and Dr. McKinley will return to present a brief history of what each has done to support this effort. After the three other speakers have finished presenting their work to support this effort, Dr. Matsumoto will join the three in a call for support by the audience. Specific issues: Need for research that support the development and continued improvement of culturally sensitive treatment modalities. Need for training of culturally sensitive treatment modalities. Need for establishment of Japanese laws protecting confidentiality of the medical records.